Respon Pertumbuhan dan Hasil Beberapa Varietas Kubis Bunga (Brassica oleraceae L.) pada Berbagai Umur Bibit di Lahan Kering Dataran Rendah - Sandi Nurbangun; Devie Rienzani Supriadi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2021)
There are several factors that cause the production of flower cabbage fluctuate, including the cultivation system, the selection of varieties, as well as the determination of lip age. This study aims to obtain a combination of the age of seedlings and several varieties of flower cabbage (Brassica oleraceae L.). This research was conducted in the experimental land of the Faculty of Agriculture, Singaperbangsa Karawang University located in Pasirjengkol Village, Majalaya District, Karawang Regency, West Java Province. The research site was located at an elevation of 40 meters above sea level, in July – October 2020. The research method used is the experimental method and the experimental design used is a single-factor RandomIzed Design (RAK) with 8 combinations of treatments and repeated 4 times, so that there are 32 plots of experiments. The data were analyzed using variety analysis and advanced tests with multiple distance DMRT tests at a rate of 5%. The results of the study of a combination of the life of seedlings and some varieties of flower cabbage exerted a noticeable influence on the growth components (height of the plant and the number of leaves), as well as the yield components (the weight of flowers per plant, the wet weight of the header and the wet weight of the roots of the plant). In combination with the age of seedlings 21 days after seedlings (HSS) with varieties of flower cabbage PM 126 F1 gives the highest yield on crop weight of 22.46 grams / plant.